Optimal control of a sex‐structured HIV/AIDS model with condom use - Magombedze, Gesham; Mukandavire, Zindoga; Chiyaka, Christinah; Musuka, Godfrey (Mathematical Modelling and Analysis, 2009)
Optimal control theory is applied to a sex‐structured HIV/AIDS model with condom use as an intervention strategy. An objective functional to maximise condom use in a population and minimise cases of infectious HIV is adopted. The optimal control is characterised and solved numerically. Simulation results suggest that high percentage of condom usage is associated with reduced HIV incidence, while high costs of condom usage campaigns reduces the percentage condom usage. Targeting issuance of condoms to infectious individuals enables reduction of condom usage campaign costs, hence ensures high percentage of condom usage. First published online: 14 Oct 2010